The man-machine integration era - Bilar, Daniel (PeerJ Preprints, 2016)
Through sensor ubiquity, the man-machine integration era is upon us. This integration is taking place in distributed, continuously changing, optimizing/learning, finite precision feedback systems. Security challenges of such systems abound, also due to constantly co-evolving threat actors and changing environments. Are we adequately preparing to defend such systems, and more importantly: how do we ensure they are worth defending? This position paper posits we are ill-prepared, due to perverse incentives affecting methodology, results and foundational corpuses. With respect to the first question, we will corroborate this ill-preparedness in the context of a basic requirement – situational awareness – for so-called Moving Target Defenses. We’ll argue that the second question hinges on a deceptively straightforward permanence invariant: The ability to robustly encode the infinite value of a human being in finite precision systems. Here too, we are failing to develop needed toolsets and skills. Successfully tackling both questions may determine the future winning model of the man-machine integration era; whether we’ll lose the Republic of the People to the People’s Republic.
Keywords: Distributed Systems; Moving Target Defenses; Education; Security Science; Invariants; China; Optimization